Recent developments in phase theory - Craenenbroeck, Jeroen van, 1976-; Cavirani-Pots, Cora 1990-; Temmerman, Tanja (Studies in generative grammar ;, 2020)
"The overarching goal of this volume is to explore a number of recent developments in Phase Theory (both theoretical and empirical), thus contributing to our overall understanding of the concept of phases.The volume is divided into three parts, of which the first focuses on the traditional role played by phases in defining successive cyclicity, while at the same time examining the interaction between that traditional role and Chomsky (2013)'s proposal about labeling. The second part focuses on the question of whether only the highest projection of the clausal and nominal domain, CP and DP, are phases or whether those domains also contain an internal phase: vP and NP/NumP/QP, while the third part contains two chapters that focus on the extent to which ellipsis can be used as a reliable diagnostic for phasehood.As a whole, the volume provides a detailed and in-depth view on a number of recent developments in Phase Theory, which will likely continue to dominate the debate for several years to come."--